The Effect of User Perception and User Experience on Customer Loyalty in Digital Mobility Platforms: Implications for Management Education (A Study of Gojek Indonesia) - Terensia Tobing; Erna Listiana; Giriati; Barkah Barkah; Ana Fitriana (Al-Qalam Institue, 2026)
The rapid development of application-based ride-hailing services has intensified market competition and encouraged service providers to better understand the factors influencing customer satisfaction and loyalty. This study aims to examine the effects of perceived price fairness, e-service quality, and wayfinding on customer loyalty, with customer satisfaction serving as a mediating variable among users of the Gojek application in Indonesia. Using a quantitative approach, data were collected through an online survey of 218 respondents selected via purposive sampling, and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 3. The results indicate that perceived price fairness, e-service quality, and wayfinding have positive and significant effects on customer satisfaction, while e-service quality and customer satisfaction have positive and significant effects on customer loyalty. Furthermore, the indirect effect analysis confirms that customer satisfaction significantly mediates the relationships between perceived price fairness, e-service quality, and wayfinding and customer loyalty. These findings highlight that customer loyalty in digital ride-hailing services is more strongly shaped through customer satisfaction resulting from users’ comprehensive evaluations of price fairness, digital service quality, and application navigation, and provide important managerial and management education implications for understanding customer-oriented digital service management.